Contractual Fragility, Job Destruction, and Business Cycles - Ramey, G.; Watson, J. (Quarterly Journal of Economics, 1997)
We develop a theory of labor contracting in which negative productivity shocks lead to costly job loss, despite unlimited possibilities for renegotiating wage contracts. Such fragile contracts emerge from firms' trade-offs between robustness of incentives in ongoing employment relationships and costly specific investment. Contractual fragility can serve as a powerful mechanism for propagating underlying productivity shocks: in a simulated matching market equilibrium, i.i.d. shocks are greatly magnified in their effect on market output, and the effect is highly persistent. We also explore novel motivations for government policies that strengthen employment relationships.